Combined Immunosuppressive Therapy (Corticosteroid-Cyclosporine) on Hospital Stay in Patients with SevereCutaneous Adverse Reactions perspective of health worker: A Qualitative Study - Widhiati, Suci; -, Hastika Dwi Oktiningrum; Tansil, Ivana; Arrosyid, Azhar (Rumah Sakit Umum Daerah Dr. Moewardi, 2025)
IntroductionSevere cutaneous adverse reactions (SCARs) such as Stevens-Johnson Syndrome (SJS), Toxic Epidermal Necrolysis (TEN), and DRESS are rare but life-threatening conditions requiring intensive inpatient care. Corticosteroids remain the main therapy but may prolong hospitalization and increase complications. Combining corticosteroids with cyclosporine has been considered to improve patient outcomes. This study explored healthcare professionals’ perspectives on the impact of this therapy combination on hospitalization duration for SCAR patients. MethodsA qualitative exploratory study was conducted at Dr. Moewardi General Hospital, Surakarta (August–October 2023). Purposive sampling recruited 12 healthcare professionals (3 consultants, 5 residents, 4 nurses) involved in SCAR management. Semi-structured interviews explored diagnostic confidence, treatment approaches, and hospitalization duration. Data were analyzed using thematic analysis. ResultPhysicians reported high diagnostic confidence, with typical hospital stays ranging from 14–30 days. Most favored corticosteroid–cyclosporine combination therapy, perceiving faster recovery and fewer complications. Barriers included limited drug availability, unfamiliarity with dosing, and safety concerns. Nurses emphasized wound care challenges, infection risks, and psychosocial needs. Both groups underlined the importance of multidisciplinary collaboration and family involvement in optimizing patient outcomes. ConclusionHealthcare professionals perceive corticosteroid–cyclosporine combination therapy as potentially effective in shortening hospitalization and reducing complications among SCAR patients. Institutional support, clinician training, and further clinical research are recommended to strengthen its implementation.